Singular Factorization of an Arbitrary Matrix - Thapa, Gyan Bahadur; Lam-Estrada, P.; López-Bonilla, J. (Journal of the Institute of Engineering, 2017)
In this paper, we study the Singular Value Decomposition of an arbitrary matrix Anxm, especially its subspaces of activation, which leads in natural manner to the pseudo inverse of Moore -Bjenhammar - Penrose. Besides, we analyze the compatibility of linear systems and the uniqueness of the corresponding solution and our approach gives the Lanczos classification for these systems. Journal of the Institute of Engineering, 2016, 12(1): 77-86